2017
DOI: 10.3389/fnhum.2017.00095
|View full text |Cite|
|
Sign up to set email alerts
|

Language Learning Enhanced by Massive Multiple Online Role-Playing Games (MMORPGs) and the Underlying Behavioral and Neural Mechanisms

Abstract: Massive Multiple Online Role-Playing Games (MMORPGs) have increased in popularity among children, juveniles, and adults since MMORPGs’ appearance in this digital age. MMORPGs can be applied to enhancing language learning, which is drawing researchers’ attention from different fields and many studies have validated MMORPGs’ positive effect on language learning. However, there are few studies on the underlying behavioral or neural mechanism of such effect. This paper reviews the educational application of the MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 79 publications
1
27
0
1
Order By: Relevance
“…According to Zhang et al (2017, p. 2) while many studies have argued that MMORPGs can facilitate vocabulary learning, the teacher's control in the learning activity design is imperative for pedagogical effectiveness. Apart from vocabulary development, the other identified skills as listed above concur with other studies as cited in Zhang et al (2017) that have found positive relationships between MMORPGs and basic language development. These include the impact on speaking abilities (Lai & Wen, 2012), listening skills (Hu and Chang, 2007), and interactional competence (Berns et al, 2013).…”
Section: Good Games Principles Relevant For Efl Game-based Language Lsupporting
confidence: 88%
See 1 more Smart Citation
“…According to Zhang et al (2017, p. 2) while many studies have argued that MMORPGs can facilitate vocabulary learning, the teacher's control in the learning activity design is imperative for pedagogical effectiveness. Apart from vocabulary development, the other identified skills as listed above concur with other studies as cited in Zhang et al (2017) that have found positive relationships between MMORPGs and basic language development. These include the impact on speaking abilities (Lai & Wen, 2012), listening skills (Hu and Chang, 2007), and interactional competence (Berns et al, 2013).…”
Section: Good Games Principles Relevant For Efl Game-based Language Lsupporting
confidence: 88%
“…The impact of computer-based gaming or online games on language learning have especially been significant. Studies on the use of virtual environments and online games in language learning have found benefits ranging from increased motivation and engagement to enhanced vocabulary gains, as well as expanded opportunities for communicative competence (Ariffin, 2012;Berns et al, 2013;Zhang & Kaufman, 2015;Hong et al, 2016;Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…left anterior insular/frontal operculum and visual word form area) [63]. Moreover, the attentional bias toward information relevant to the task was identified as the possible mechanism for facilitated L2 learning in MMORPGs in that the activation in DLPFC, parahippocampal gyrus and thalamus was higher in players of MMORPGs in the response to VG-related cues compared to neutral cues [63]. That is, playing MMOR-PGs are suggested to support L2 learning.…”
Section: Sgsmentioning
confidence: 98%
“…The last cognitive function that is identified to be positively associated with VG is second language (L2) learning in that not only serious games but also commercial VGs provide players with the opportunity for language practice and acquisition [60]. Among various genres, MMORPGs, which are full with the opportunity of interaction between players, and between players and the VG environment in target language [61], are suggested as the efficient method for speaking practice [62] and are reported to facilitate the learning of L2 [63]. Players engaging in frequent interaction in VG environments were found to show strengthened functional connectivity (FC) within brain regions involved in language processing (i.e.…”
Section: Sgsmentioning
confidence: 99%
See 1 more Smart Citation